### Home > INT3 > Chapter 7 > Lesson 7.1.4 > Problem 7-48

7-48.

What is the inverse of each of the functions below? Write your answers using function notation. Homework Help ✎

*p*(*x*) = 3(*x*^{3}+ 6)*k*(*x*) = 3*x*^{3}+ 6*h*(*x*) =*j*(*x*) =

Let *p*(*x*) = *y*, switch the *x* and the *y* in the equation and solve for *y*.

See part (a).

Let *h*(*x*) = *y* . Switch *x* and *y*. Multiply both sides of the equation by (*y* − 1) to remove the fraction.

Distribute and then rewrite the equation so that all the *y*-terms are on the left side and everything else is on the right side.

Your equation should look like this: *xy* − *y* = *x* + 1. Factor the left side of the equation and divide both sides by (*x* − 1) to get *y* by itself.

Graph the equation on a graphing calculator to see why this equation is its own inverse.

See part (a).